Time, defeasible logic and belief revision: pathways to legal dynamics - Tamargo, Luciano Héctor (2021)
In order to properly model norm change in the law, temporal aspects of legal dynamics must be considered. Since there exist several time-based features of law that should be studied, we discuss two interesting approaches: one based on defeasible logic and the other based on belief revision. Each of these makes use of one of the two classic forms of reasoning about time: point-based and interval-based. Both formalisms provide the necessary logical infrastructure to address the characterization of complex behaviour of legal dynamics.